Boards of directors of state-owned enterprises. An overview of national practices (Paris, 2013)
"Boards of directors of state-owned enterprises (SOEs) play a fundamental role in corporate stewardship and performance. Over the last decade, OECD governments have sought to professionalise SOE boards, ensure their independence and shield them from ad hoc political intervention. In general these approaches have worked; yet, more remains to be done to meet the aspirational standards of established by the OECD Guidelines on Corporate Governance of State-Owned Enterprises. This report seeks to shed slight on good practices drawing on national practices from over 30 economies."